DENTAL CARIES LEADING TO PREMATURE LOSS OF BABY TEETH- IMPLICATIONS AND MANAGEMENT - Bahuguna, Rachana; Narain, Sansriti; Singh, Tapan (Indian Journal of Community Health, 2011)
Dental caries is a destructive process causing decalcification of the tooth enamel and leading to continued destruction of enamel and dentin, and cavitation of the tooth. Dental caries can occur soon after eruption of the primary teeth, starting at 6 months of age. Primary teeth are present for a reason. One key reason is that they save space for the permanent tooth, which will erupt into its position when the deciduous / primary tooth is lost normally. If a primary tooth (baby or milk tooth), has to be removed early due to say, an abscess which is mostly a result of dental caries, a space maintainer may be recommended to save the space. If the space is not preserved, the other teeth may drift causing difficult to treat crowding and orthodontic problems. These "spacers" are placed temporarily, and are not permanent. They are removed when the new tooth (usually a bicuspid) erupts or the abutment teeth get loose.